Hubungan antara Fasilitas Kampus terhadap Motivasi Belajar Mahasiswa di Lingkungan Perkuliahan (Studi Kasus pada Mahasiswa Fakultas Vokasi Universitas Airlangga) - Abdan Yusri Arrizqi; Via Layli Mukarromah; Pandika Ardi Herwanto (Teewan Journal Solutions, 2025)
This study aims to analyze the causality between campus facilities and students' learning motivation within the campus environment, focusing on students of the Vocational Faculty at Universitas Airlangga. The research employs a quantitative method with a descriptive design and Pearson correlation test. The population comprises 5,894 students, and a sample of 100 was determined using proportional stratified random sampling techniques. The research instrument is a 5-point Likert Scale questionnaire measuring perceptions of campus facilities (variable X) and learning motivation (variable Y). The findings confirm a significant negative causality between campus facilities and students' learning motivation (r = -0.619, p < 0.05). Sub-variables such as laboratory facilities (r = -0.658) and library facilities (r = -0.631) significantly influence learning motivation, whereas sub-variables like green areas and gazebos show insignificant causality (r = -0.166, p > 0.05). These findings indicate that facilities directly related to academic learning have a greater impact on student motivation compared to non-academic facilities. This study implies that higher education administrators should prioritize improving facilities relevant to students' academic needs, such as laboratory completeness and stable Wi-Fi access. Future research recommendations include expanding the population scope and adopting qualitative methods to gain deeper insights into students' perceptions of campus facilities.